Вплив магнітно-абразивного оброблення на якість шпонкових фрез із швидкорізальної сталі - Майборода, Віктор Станіславович; Слободянюк, Іванна Валентинівна; Джулій, Дмитро Юрійович; Тарган, Дмитро Валентинович (НТУ "ХПІ", 2018)
Досліджено вплив швидкості обертання шпонкових фрез виготовлених з швидкорізальної сталі навколо власної осі в процесі магнітно-абразивного оброблення в робочих зонах кільцевого типу та складу магнітно-абразивного інструменту на показники якості. Встановлено, що збільшення швидкості обертання фрез навколо власної осі в досліджуваному діапазоні призводить до підвищення поверхневої твердості, зменшує інтенсивність формування радіусу округлення різальних кромок та суттєво не впливає на зміну шорсткості робочих поверхонь. Проведено дослідження працездатності шпонкових фрез після циклу магнітно-абразивного оброблення, показано, що відбувається підвищення їх стійкості в 2 і більше рази в порівнянні з необробленими. Встановлено, що найбільше на працездатність впливає величина та форма радіусу округлення різальних кромок та поверхнева твердість різального інструменту.

Experimental investigations of influences of magneto-abrasive machining conditions on the quality parameters of keyway mills made of high speed steel were carried out. It was determined that an increasing in angular velocity of mills around its own axis during the machining does not lead to the intensification reducing of roughness parameters and formation radiuses of cutting edge rounding. But it increases the hardness of working surfaces due to the frictional hardening. The best results for hardening were obtained at using powdered with round shape, which provides increasing of hardness to value 10-11,5 GPa at the initial 8-9 GPa, reduction of roughness at using splinter powders with high abrasive ability, which provides value of Ra 0,45 µm at the initial 1,4 µm. By using the method of magneto-abrasive machining can be increased the keyway mills tool life by forming the necessary size of radiuses of cutting edge rounding and increasing of the hardness of the surface layers of the working elements. Experimen tally was investigated that at the angular velocity of mills around its own axis 500 rpm and using as magneto-abrasive material the diffuse powder made from PR R6M5 with grain size 160/100 µm the tool life increases in 2-2,3 times.
Influence of magneto-abrasive machining on the quality keyway mills made of high speed steel
Keywords: твердість; шорсткість; різальна кромка; зношення; різальний інструмент; hardness; roughness; cutting edge